Identification of a novel ANK1 gene variant c.1504-9G>A and its mechanism of intron retention in hereditary spherocytosis - Xiong, Ting; Xu, Zhongjin; Wan, Qian; Chen, Feng; Ye, Yao; Wang, Hong; Wu, Chongjun (Frontiers in Genetics, 2024)
Objective: The objective of this study was to pinpoint pathogenic genes and assess the mutagenic pathogenicity in two pediatric patients with hereditary spherocytosis. Methods: We utilized whole-exome sequencing (WES) for individual analysis (case 1) and family-based trio analysis (case 2). The significance of the intronic mutation was validated through a Minigene splicing assay and supported by subsequent in vitro experiments. Results: Both probands received a diagnosis of hereditary spherocytosis. WES identified a novel ANK1 c.1504-9G>A mutation in both patients, causing the retention of seven nucleotides at the 5' end of intron 13, as substantiated by the Minigene assay. This variant results in a premature stop codon and the production of a truncated protein. In vitro studies indicated a reduced expression of the ANK1 gene. Conclusions: The novel ANK1 c.1504-9G>A variant is established as the causative factor for hereditary spherocytosis, with the c.1504-9G site functioning as a splicing receptor.